Analysis of Teacher Pedagogical Competence in Learning Process of Fifth Grade in Sabdoguno Cluster, Alian Sub-District, Kebumen Regency - Amanah, Laras Tazkiatul; Suryandari, Kartika Chrysti; Joharman, Joharman (Kalam Cendekia: Jurnal Ilmiah Kependidikan, 2020)
Abstract: Analysis of Teacher Pedagogical Competence in Learning Process of Fifth Grade in Sabdoguno Cluster, Alian Sub-District, Kebumen Regency. The objectives of the study were to analyze teacher pedagogical competence in: (1) learning planning, (2) learning. It was a qualitative research. The data were sentences or researchers narratives about research subjects. Data collection techniques were obtained from observation, interviews, and questionnaires. The participants were 6 teachers of fifth grade and school principal in the Sabdoguno cluster. Data validity techniques used triangulation of source and triangulation of technique. Data analysis techniques were data reduction, data presentasion, and verification. Teacher pedagogical competence in the learning planning and learning process, were analyzed during learning activities. The study indicates that Teachers pedagogical competence greatly determines the success of the learning to process.The implementation of learning is not separated from the learning to plan prepared by the teacher. Competent teachers can manage learning well and enhance students learning passion and improve learning quality. Keywords : pedagogical competence, teacher, learning